Safety and effectiveness of the Low Profile Visualized Intraluminal Support (LVIS and LVIS Jr) devices in the endovascular treatment of intracranial aneurysms: results of the TRAIL multicenter observational study. (24th November 2017) - Iosif, Christina; Piotin, Michel; Saleme, Suzana; Barreau, Xavier; Sedat, Jacques; Chau, Yves; Sourour, Nader; Aggour, Mohamed; Brunel, Herve; Bonafe, Alain; Machi, Paolo; Riquelme, Carlos; et al.
Abstract : Background and purpose: To evaluate the safety and effectiveness of the low-profile braided intracranial stents called the Low Profile Visualized Intraluminal Support (LVIS) devices for stent-assisted coil embolization of wide-necked intracranial aneurysms. Materials and methods: This was a prospective, multicenter, observational study of unruptured and ruptured intracranial aneurysms treated with the LVIS devices. Imaging and clinical data were independently analyzed respectively by CoreLab and Clinical Event Committee. Primary endpoints were clinical safety, effectiveness, and angiographic stability of the results at 6 and 18 months. Results: Ten centers participated in the study; 102 patients were included and 90 patients (42.2% men, 57.8% women) were eventually analyzed, among which 27 (30.0%) had multiple aneurysms. Twenty-three (25.6%) were ruptured aneurysms, four of which (4.4%) were treated in the acute phase. One aneurysm was treated per patient; 92 LVIS and LVIS Jr devices were placed overall. The total aneurysm occlusion rate was 91.0% on immediate post-procedure angiograms, which remained unchanged at 6-month follow-up and was 92.4% at 18-month follow-up. One patient (1.1%) underwent retreatment between 6 and 18 months of follow-up. A modified Rankin score of 0 was documented for most cases immediately after the procedure (86.7%) and at 6-month (86.8%) and 18-month (83.3%) follow-up. The overall permanent morbidity rate at 18 months was 5.6% and the overall rate of events with sequelae related to the stent was 2.2%. The 18-month procedure-related mortality rate was 3.3%. No patient was deemed to require retreatment at 18-month follow-up. Conclusion: The LVIS/LVIS Jr endovascular devices are safe and effective in the treatment of ruptured and unruptured intracranial aneurysms, with acceptable complication rates, very high immediate total occlusion rates, and stable angiographic results.